Most people will continue on dissatisfied but never attempting to understand why - Stobbe, Morgan (My University, 2015)
Under the premise that the visual form is dictated by the content, students were encouraged to analyze plot, characters, point of view, imagery, tone, themes and symbolism to extract keywords, sentences and passages as the basis for their designs. Students were asked to challenge literal interpretations by exploring the use of expressive typography and text and image relationships.
Displayed March 4-31, 2015 at MacEwan University Library, City Centre Campus in Edmonton, Alberta.
Keywords: typography; poster design; The Sisters Brothers; Patrick deWitt; MacEwan Book of the Year